Cardiological parameters predict mortality and cardiotoxicity in oncological patients - Romann, Sebastian W.; Finke, Daniel; Heckmann, Markus B.; Hund, Hauke; Giannitsis, Evangelos; Katus, Hugo; Frey, Norbert; Lehmann, Lorenz (ESC heart failure, 2024)
Aims Oncological patients suspected at risk for cardiotoxicity are recommended to undergo intensified cardiological surveillance. We investigated the value of cardiac biomarkers and patient-related risk factors [age, cardiovascular risk factors (CVRFs), and cardiac function] for the prediction of all-cause mortality (ACM) and the development of cardiotoxicity. Methods and results Between January 2016 and December 2020, patients with oncological diseases admitted to the Cardio-Oncology Unit at the Heidelberg University Hospital were included. They were evaluated by medical history, physical examination, 12-lead electrocardiogram, 2D echocardiography, and cardiac biomarkers [high-sensitivity cardiac troponin T (hs-cTnT) and N-terminal pro-brain natriuretic peptide (NT-proBNP)]. The primary endpoint was defined as ACM and the secondary endpoint was defined as cardiotoxicity, as defined by the European Society of Cardiology. Of the 1971 patients enrolled, the primary endpoint was reached by 490 patients (25.7%) with a median of 363.5 [interquartile range (IQR) 121.8, 522.5] days after presentation. Hs-cTnT of ≥ 7 ng/L [odds ratio (OR) 1.82, P < 0.001] and NT-proBNP (OR 1.98, P < 0.001) were independent predictors of ACM, while reduced left ventricular ejection fraction was not associated with increased ACM (P = 0.85). The secondary endpoint was reached by 182 patients (9.2%) with a median of 793.5 [IQR 411.2, 1165.0] days. Patients with multiple CVRFs (defined as high risk, n = 886) had an increased risk of cardiotoxicity (n = 100/886, 11.3%; hazard ratio 1.57, P = 0.004). They showed elevated baseline values of hs-cTnT (OR 1.60, P = 0.006) and NT-proBNP (OR 4.00, P < 0.001) and had an increased risk of ACM (OR 1.43, P = 0.031). Conclusions In cancer patients, CVRF accumulation predicts cardiotoxicity whereas elevated hs-cTnT or NT-proBNP levels are associated with ACM. Accordingly, less intensive surveillance protocols may be warranted in patients with low cardiac biomarker levels and absence of CVRFs.
Online veröffentlicht: 27 November 2023
Gesehen am 15.01.2024